2011
DOI: 10.1177/1363461511404623
|View full text |Cite
|
Sign up to set email alerts
|

Cultural epidemiology of neurasthenia spectrum disorders in four general hospital outpatient clinics of urban Pune, India

Abstract: Disorders emphasizing symptoms of fatigue and/or weakness, collectively termed Neurasthenia Spectrum Disorders (NSDs), typically emphasize a biological basis in the West and social origins in East Asia. In India, explanatory concepts are diverse. To clarify, 352 outpatients in Psychiatry, Medicine, Dermatology, and Ayurved clinics of an urban hospital were interviewed with a version of the Explanatory Model Interview Catalogue. Comparisons of categories and narratives of illness experience and meaning across c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In an Indian study, significantly more women with features of neurasthenia spectrum disorder had identified marital problem as the most important perceived cause for their suffering, while none of the men did so [28]. Similar results from this study can be explained as patients are from the similar cultural background (Table 3).…”
Section: Discussionsupporting
confidence: 75%
“…In an Indian study, significantly more women with features of neurasthenia spectrum disorder had identified marital problem as the most important perceived cause for their suffering, while none of the men did so [28]. Similar results from this study can be explained as patients are from the similar cultural background (Table 3).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, there are the Short Explanatory Model Interview (Lloyd et al, 1998), the Mental Distress Explanatory Model Questionnaire (Eisenbruch, 1990), and the Barts Explanatory Model Inventory (Bhui, Ru¨dell, & Priebe 2006). For applications of these research tools in India see Banerjee & Banerjee, 1995, p. 219; see also Campion & Bhugra, 1997;Banerjee & Roy, 1998;Nieuwsma, Pepper, Maack, & Birginheir, 2011;Paralikar et al, 2011. Religious explanations might refer to Karma; bad or prior deeds or parent's deeds; the will of God(s); fate; deities and demons; the evil eye; astrological factors; spiritual deficits; sorcery; or other supernatural factors (see Nieuwsma et al, 2011, p. 549).…”
Section: Resultsmentioning
confidence: 97%
“…[ 11 ] Diverse and rapidly changing cultural features of Indian urban patients and clinicians pose a challenge as well as an opportunity to test the CFI. Cultural epidemiological studies[ 12 ] using EMIC interviews had influenced the development of the CFI.…”
Section: Introductionmentioning
confidence: 99%